Analysis of the current situation and influencing factors of emotional labor among pediatric nurses: A cross-sectional study - Huiqing Liu; Zifeng Li; Xiaojing Zhou; Wei Gong; Zuyang Xi; Juan Cao (PLoS ONE, 2026)
Aim To examine the level and factors associated with emotional labor among pediatric nurses in Yichang, China. Methods From December 20–25, 2024, a cross-sectional descriptive online study was conducted among 307 pediatric nurses in Yichang, China. The survey included general information, emotional labor (assessed using the Emotional Labor Scale; higher scores indicate greater emotional labor), spiritual climate, and compassion satisfaction, and the influencing factors associated with emotional labor were analyzed. Results Pediatric nurses in Yichang had a total emotional labor score of 69.20 ± 9.40. Regression analysis showed that nurses without children had higher emotional labor levels than those with children (P < 0.05). Higher spiritual climate and compassion satisfaction scores were both significantly associated with higher emotional labor scores (P < 0.05). Conclusions The intensity of emotional labor among pediatric nurses in Yichang is high and is associated with parental status (having children), spiritual climate, and compassion satisfaction.